Proof of J is a Radical Class Using Amitsur Theorem (Global Journal of Science Frontier Research, 2012)
The aim of this paper is to study radical class of rings, right quasi-regular rings and finally, to prove that J , the class of all right quasi-regular rings is a radical class. Amitsur gives a theorem of radical class for the sufficient condition that a class of rings would be a radical class. This paper represents, the proof of, J is a radical class using the theorem of radical class given by Amitsur.
Keywords: Ring; Ideal; Radical Class; Right quasi-regular ring